Interpretation of cone penetration test data in layered soils using cavity expansion analysis - Mo, Pin-Qiang; Marshall, Alec M.; Yu, Hai-Sui (American Society of Civil Engineers, 2016)
Cavity expansion theory plays an important role in many geotechnical engineering problems, including the cone penetration test (CPT). One of the challenges of interpreting CPT data is the delineation of interfaces between soil layers and the identification of distinct thin layers, a process which relies on an in-depth understanding of the relationship between penetrometer readings and soil properties. In this paper, analytical cavity expansion solutions in two concentric regions of soil are applied to the interpretation of CPT data, with a specific focus on the layered effects during penetration. The solutions provide a large-strain analysis of cavity expansion in two concentric regions for dilatant elastic-perfectly plastic material. The analysis of CPT data in two-layered soils highlights the effect of respective soil properties (strength, stiffness) on CPT measurements within the influence zones around the two-soil interface. Results show good comparisons with numerical results and elastic solutions. A simple superposition method of the two-layered analytical approach is applied to the analysis of penetration in multilayered soils. A good comparison with field data and numerical results is obtained. It is illustrated that the proposed parameters effectively capture the influence of respective soil properties in the thin-layer analysis. It is also shown that results based on this analysis have better agreement with numerical results compared with elastic solutions.